2019
DOI: 10.1371/journal.pone.0226154
|View full text |Cite
|
Sign up to set email alerts
|

Amiselimod (MT-1303), a novel sphingosine 1-phosphate receptor-1 functional antagonist, inhibits progress of chronic colitis induced by transfer of CD4+CD45RBhigh T cells

Abstract: Amiselimod (MT-1303) is a novel sphingosine 1-phosphate receptor-1 (S1P1 receptor) modulator with a more favorable cardiac safety profile than other S1P1 receptor modulators. MT-1303 phosphate (MT-1303-P), an active metabolite of MT-1303, exhibits S1P1 receptor agonism at a lower EC50 value than other S1P1 receptor modulators currently being developed. We aimed to evaluate the efficacy of MT-1303 and its mode of action in chronic colitis using an inflammatory bowel disease (IBD) model. Oral administration of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…We have reported that fingolimod, the first S1P 1 receptor modulator, reduces infiltration of myelin antigen-specific Th17 and Th1 cells into the spinal cord [15]. Further, we have also confirmed that MT-1303 inhibits infiltration of colitogenic Th1 and Th17 cells into the colon in a mouse IBD model [30]. These results suggest that MT-1303 decreases infiltration of autoreactive Th1, Th17, and DN T cells into the kidneys by reducing the number of circulating lymphocytes in the blood, thereby eliciting a marked therapeutic effect on the progression of lupus nephritis in two SLE models.…”
supporting
confidence: 64%
“…We have reported that fingolimod, the first S1P 1 receptor modulator, reduces infiltration of myelin antigen-specific Th17 and Th1 cells into the spinal cord [15]. Further, we have also confirmed that MT-1303 inhibits infiltration of colitogenic Th1 and Th17 cells into the colon in a mouse IBD model [30]. These results suggest that MT-1303 decreases infiltration of autoreactive Th1, Th17, and DN T cells into the kidneys by reducing the number of circulating lymphocytes in the blood, thereby eliciting a marked therapeutic effect on the progression of lupus nephritis in two SLE models.…”
supporting
confidence: 64%
“…In this regard, S1P 4 , as discussed previously in this review, is predominantly expressed in lymphoid tissues [88,95], and ligation and its subsequent signaling are involved in marking time regarding proliferation [286,287], a reduction of effector cytokines secreted [286,287], and migration of lymphocytes [288,289]. It is worth noting that amiselimod displays a very safe risk profile [290][291][292], while it is too early to consistently assess this for etrasimod [293]. Their application and/or investigation regarding their future therapeutic exploitability in neurological conditions should find due consideration soon.…”
Section: Insights Into Current and Future Therapeutic Perspectivesmentioning
confidence: 72%
“…The results demonstrated that amiselimod regulates lymphocyte trafficking, limits infiltration of colitogenic Th1 and Th17 cells into the colon, and inhibits the development of chronic colitis. 91 The investigation of the effects of amiselimod in moderate-to-severe, active Crohn's disease in a 14-week, randomised, placebo-controlled, phase II trial 92 with an open-label extension of ≥22 weeks 93 has been completed. However, amiselimod 0.4 mg/d for 12 weeks did not show a significant effect on clinical or biochemical disease activity in refractory Crohn's disease.…”
Section: Follow-up Measuresmentioning
confidence: 99%